Տարբեր բնույթի դեղամիջոցների ազդեցության գնահատումը էթանոլով սուր, ծանր թունավորման ժամանակ - Մարկոսյան, Ա. Մ. (ՀՀ ԳԱԱ «Գիտություն» հրատ.)
Представлена сравнительная оценка эффективности нейропептида семакса, гепатопротекторов с пептидным компонентом моликсана и непептидной природы гептрала, при острой, крайне тяжелой интоксикации этанолом по показателям суточной выживаемости, средней продолжительности жизни, неврологическому статусу, состоянию некоторых витальных функций организма. Этанол в виде 40% раствора вводили внутрижелудочно в дозе 1,5 ЛД50 и 2 ЛД50 (12 и 16 г/кг), семакс – интраназально в дозе 3 мг/кг, моликсан – внутрибрюшинно в дозе 30 мг/кг, гептрал – внутрибрюшинно в дозе 35 мг/кг. Эффективность препаратов оценивали при профилактической (однократно за 1 ч до этанола), лечебно-профилактической (за 1 ч до и сразу после введения этанола), ранней лечебной (сразу после введения этанола, а затем один раз в день в течение 2 последующих суток) и отсроченной лечебной (через 30 мин после введения этанола, а затем один раз в день в течение 2 последующих суток) схемах применения. Установлено, что при интоксикации, вызванной введением 1,5 ЛД50 этанола, профилактическое применение моликсана и комбинации моликсана с семаксом значительно снижало степень тяжести отравления, уменьшало количество животных, находившихся в терминальной коме в 4,9 и 2,5 раза соответственно, увеличивало выживаемость крыс на 66%. При лечебно- профилактическом применении моликсана, семакса и их комбинации выживаемость крыс была такая же, как и в случае применения гептрала. При раннем лечебном применении моликсана, а также при отсроченном лечебном применении моликсана с семаксом выживаемость отравленных крыс повышалась на 66%, при этом гептрал был не эффективен. При введении этанола в дозе 2 ЛД50 ни один из исследованных препаратов не оказал влияния на выживаемость отравленных крыс. Однако в отличие от гептрала, моликсан, семакс и их комбинация при профилактическом, лечебно-профилактическом и раннем лечебном применении способствовали увеличению средней продолжительности жизни крыс в 2,5–7,8 раза. This study presents a comparative evaluation of the neuropeptide Semax and hepatoprotectors with peptide components, specifically Molixan, and the non-peptide compound Heptral, in the context of extreme acute ethanol poisoning. The efficacy of these preparations was assessed based on parameters such as survival rate, average lifespan, neurological status, and the state of several vital functions of the organism. Ethanol at 40% concentration was administered orally at dosages of 1,5 LD50 and 2 LD50 (12 g/kg and 16 g/kg, respectively). Semax was administered intranasally at a dosage of 3 mg/kg per day, while Molixan was injected intraperitoneally at 30 mg/kg per day, and Heptral was injected intraperitoneally at 35 mg/kg per day. The efficacy of the preparations was evaluated according to the following treatment schedules: (1) preventive application (single administration 1 hour before ethanol administration), (2) therapeutic and preventive application (1 hour before and immediately after ethanol administration), (3) early treatment (immediately after ethanol administration for 2 consecutive days), and (4) delayed treatment (30 minutes after ethanol administration for 2 consecutive days). It was found that in cases of intoxication induced by 1,5 LD50 of ethanol, the preventive application of Molixan or the combination of Molixan and Semax significantly reduced the severity of poisoning, decreasing the number of animals in terminal coma by 4,9 and 2,5 times, respectively, and increasing the survival rate of the rats by 66%. When administered therapeutically and preventively, Molixan, Semax, and their combination improved the survival rate of the rats more effectively than Heptral. In cases of early therapeutic application of Molixan and its combinations with Semax, as well as delayed therapeutic application of Molixan and Semax, the survival rate of poisoned rats increased, whereas Heptral was ineffective when administered under the same conditions. None of the studied drugs had a significant effect on the survival rate of poisoned rats at the 2 LD50 ethanol dosage. However, unlike Heptral, Molixan, Semax, and their combinations, when applied preventively, therapeutically, and as a preventative measure, significantly increased the average lifespan of rats exposed to 2 LD50 of ethanol by 2,5 to 7,8 times.
Keywords: Թունավորում